Islamic political identity in Turkey - Yavuz, M. Hakan (Religion and global politics., 2003)
In November of 2002, the Justice and Development Party swept to victory in the Turkish parliamentary elections. Because of the party's Islamic roots, its electoral triumph has sparked a host of questions both in Turkey and in the West: Does the party harbor a secret Islamist agenda? Will the new government seek to overturn nearly a century of secularization stemming from Kemal Ataturk's early-twentieth-century reforms? Most fundamentally, is Islam compatible with democracy? In this penetrating work, M. Hakan Yavuz seeks to answer these questions, and to provide a comprehensive analysis of Isla.